Trends of concept analysis in nursing science with Walker and Avant approaches: a literature review - Indrayani, Ni Luh Dwi (Universitas Muhammadiyah Magelang, 2025)
Walker and Avant have been pivotal in guiding researchers toward publishing concept analysis articles. However, limited studies have explored the trends of concept analysis within the nursing context. This topic is particularly relevant today as it can inspire and inform future concept analysis publications. This study utilized a literature review design to examine the evolution of concept analysis in nursing. A total of 54 articles were identified through a systematic search across six databases. These articles were categorized into four key themes: psychological responses, healthcare system improvement, behavior, and patient-focused concepts. A comprehensive table was developed to summarize how each concept was defined by scholars, and trends over a five-year period were analyzed. The findings revealed that psychological responses were the most frequently studied theme and vice versa, research focusing on behavior showed a decline over time. Despite this trend, patient-centered concepts demonstrated consistent attention throughout the period. The study also highlighted a consistent emphasis on understanding psychological impacts and promoting patient involvement in decision-making processes. Based on these findings, future research should focus on developing caring interventions that address patients' psychological needs. Such research will further strengthen the role of nursing in fostering holistic innovation care. Keywords: Caring intervention, concept analysis, future publication, holistic innovation, psychological needs